Impact of a Common Corporate Tax Base on the effective tax burden in Belgium - Roggeman, Annelies; Verleyen, Isabelle; Cauwenberge, Philippe Van; Coppens, Carine (Journal of Business Economics and Management, 2014)
In March 2011, the European Commission launched a proposal for a Common Consolidated Corporate Tax Base (CCCTB). However, a Common Corporate Tax Base (CCTB), leaving consolidation and apportionment out of consideration, appears to be a more realistic proposition for corporate tax harmonization in Europe. Using the European Tax Analyzer (ETA), we simulate the impact of the CCTB on the effective tax burden in Belgium. The results show that the adoption of the CCTB increases the Belgian effective tax burden by 16%. This remarkable increase is mainly driven by the fact that national tax deductions are not allowed under CCTB. This study allows policymakers to gain insight into the size effects of certain corporate tax measures and contributes to the current discussion on corporate tax harmonization in Europe.